“O ardil da precarização” : o trabalho docente nas escolas de ensino médio em tempos de pandemia - Carvalho, Patrícia Simone da Silva (2023)
Just like the capitalist mode of production, teaching work has been remodeled according to constant crises, and structurally it is conditioned to the implications of capitalism. In the current scenario, the centrality of formal, industrialized and salaried work is being discussed, given the emergence of various forms of marginal work, essentially caused by the change from the mostly Fordist/Taylorist model to the flexible accumulation model or commonly known as Toyotism. The informality and precariousness of teaching work gain space and imply debates about its potential in overcoming unemployment and its functionality for capital. In order to deal with the precariousness of teaching work in the times of Covid-19, with a focus on the public education network in Mato Grosso - MT, it is necessary to investigate the world of work, educational policies, teacher training, social recognition, working conditions, teachers' health, among other factors that lead us to understand the profession. Faced with these questions, this research seeks to understand the professionalization and precariousness of teaching work in public schools in MT, considering the current challenges faced during the pandemic. Throughout this study, it was possible to follow the socio-historic path of teaching work and its precariousness within the educational system. This research has an exploratory bias, combined with appropriation of qualitative approaches. The results indicate that there were advances and setbacks in the scope of teaching work in the State of Mato Grosso, and, above all, establishing mediations that allowed inscribing the concrete reality as a synthesis of multiple determinations. In short, the dynamics of capital accumulation in Mato Grosso cost the precariousness of the workforce, transforming remote teaching by hand into a perverse dynamic of exploitation and precariousness of teaching work.